A preparation method for recycling and regenerating lithium iron phosphate positive electrode slurry

By using high-speed dispersion pre-dissolution and vacuum dispersion stirring in the preparation of recycled lithium iron phosphate positive electrode slurry, the difficulty of dispersion of binder and the generation of large particles is solved, and an efficient slurry preparation and environmentally friendly production process is achieved.

CN119764344APending Publication Date: 2025-04-04MIANYANG HIGH-TECH EXXON NEW ENERGY TECH CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411950751.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-27
Publication Date
2025-04-04

AI Technical Summary

Technical Problem

In the prior art, the recycled lithium iron phosphate positive electrode slurry contains binder, which leads to difficulties in dispersion, resulting in large particles causing clogging of screen mesh, and causing scratches and exposed foil during coating.

Method used

High-quality positive electrode slurry was prepared by mixing the recovered regenerated lithium iron phosphate powder with an organic solvent and dispersing at high speed, followed by adding binder, conductive agent and dispersant, and high-speed dispersion and stirring under vacuum conditions and slow foaming.

Benefits of technology

It effectively solves the problem of difficulty in dispersing binder in recycling regenerated lithium iron phosphate, reduces the generation of large particles, improves the uniformity and production efficiency of coating, and reduces the potential pollution of waste batteries to the environment.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119764344A_ABST
    Figure CN119764344A_ABST
Patent Text Reader

Abstract

The present invention discloses a method for preparing a recycled lithium iron phosphate positive electrode slurry, comprising the following steps: 1) mixing recycled lithium iron phosphate powder and an organic solvent and pre-dissolving them at high speed; 2) adding a binder powder, a conductive agent and an organic solvent, mixing and dispersing and stirring; 3) adding a dispersant and an organic solvent, dispersing and stirring at high speed under vacuum conditions, and slowly stirring and defoaming after the dispersion is completed, so as to obtain a recycled lithium iron phosphate positive electrode slurry. The present invention pre-dissolves the binder in the recycled lithium iron phosphate powder under high solid content conditions by using a pre-dissolution method, effectively solving the dispersion difficulties caused by the binder in the recycled lithium iron phosphate, reducing the blockage of the screen caused by large particles of the recycled lithium iron phosphate positive electrode slurry and the scrapping of particles, scratches, exposed foil, etc. on the appearance of the dried pole piece after coating, and effectively improving production efficiency and production benefits.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of waste battery recycling, and in particular relates to a preparation method for recycling and regenerating lithium iron phosphate positive electrode slurry. Background Art

[0002] With the popularization of electronic devices and the rapid rise of the electric vehicle industry, lithium-ion batteries play an increasingly important role, and production and sales continue to increase; in order to provide longer battery life and battery life stability, research on new lithium-ion battery materials is also advancing. The existing lithium iron phosphate cathode accounts for more than 35% of the battery cell cost, mainly because lithium resources are limited in reserves and have high value as key raw materials; therefore, the failure, waste and resource recycling of lithium-ion battery cathode materials have become increasingly important, and how to solve the problem of scrapped lithium-ion battery disposal in the downstream is gradually being put on the agenda.

[0003] In the prior art, the preparation of positive electrode slurry for lithium-ion batteries usually uses dry stirring, semi-dry stirring and wet stirring processes; wherein dry stirring is to uniformly mix the powder (including active material, conductive agent and binder) and then directly add NMP solvent for stirring; semi-dry stirring requires the preparation of PVDF glue, and the powder (active material, conductive agent) is initially premixed and then added with PVDF glue in a single step or multiple steps, and kneaded and dispersed until it is uniformly dispersed; wet stirring is to use solvent and binder to prepare glue, and then add active material and conductive agent into the glue and stir, and wet stirring usually takes a long time to ensure sufficient dispersion and mixing of materials.

[0004] However, the existing technology for recycling and regenerating lithium iron phosphate contains binders, which makes dispersion difficult, and large particles in the positive electrode slurry easily cause clogging of the screen, as well as scratches and exposed foil during coating, which can cause the coating to be scrapped. Summary of the invention

[0005] The present invention aims to solve at least one of the technical problems in the related art to a certain extent. To this end, the main purpose of the present invention is to provide a method for preparing a recycled lithium iron phosphate positive electrode slurry, which aims to solve the problems of the existing recycled lithium iron phosphate containing a binder causing dispersion difficulties, large particles of the positive electrode slurry causing screen blockage, and scratches and exposed foil during coating causing scrapping.

[0006] The objective of the present invention is achieved through the following technical solutions:

[0007] A method for preparing a recycled lithium iron phosphate positive electrode slurry comprises the following steps:

[0008] 1) mixing the recovered regenerated lithium iron phosphate powder and the organic solvent and pre-dissolving them by high-speed dispersion to obtain a first mixed material;

[0009] 2) adding binder powder, conductive agent and organic solvent to the first mixed material obtained in step 1), mixing and dispersing and stirring to obtain a second mixed material;

[0010] 3) Adding a dispersant and an organic solvent to the second mixed material obtained in step 2), performing high-speed dispersion and stirring under vacuum conditions, and performing slow stirring and defoaming after the dispersion is completed to obtain a recovered regenerated lithium iron phosphate positive electrode slurry.

[0011] In some specific embodiments, the recycled lithium iron phosphate powder in step 1) is positive electrode lithium iron phosphate powder recycled from waste lithium iron phosphate batteries.

[0012] In certain specific embodiments, the recycled lithium iron phosphate powder has D10 ≥ 0.25 μm, D50 = 1.50 ± 1.00 μm, D90 ≤ 10.00 μm, specific surface area = 10.0 ± 3.0 m2 / g, and carbon content of 2.0-4.0 wt.%.

[0013] In some specific embodiments, the organic solvent is any one or more of N-methylpyrrolidone (NMP), N-dimethylformamide, dimethyl sulfoxide, ethylene glycol or N-dimethylacetamide; the binder powder is PVDF powder; the conductive agent is a combination of one or more of carbon nanotubes, conductive graphene, conductive carbon black, and carbon fiber; and the dispersant is polyvinyl pyrrolidone.

[0014] In some specific embodiments, the mass ratio of the recycled lithium iron phosphate powder, binder powder, conductive agent, and dispersant is: 99.1-97.5: 0.3-0.8: 0.5-1.5: 0.1-0.2.

[0015] In some specific embodiments, the amount of the first organic solvent added in step 1) accounts for 20% to 25% of the total mass of the first mixture, and the solid content of the first mixture is 75% to 80%.

[0016] Furthermore, in step 1), the dispersion rotation speed of the high-speed dispersion pre-dissolution is 1200rpm to 1500rpm, the dispersion revolution speed is 20rpm to 25rpm, and the dispersion time is 120min to 240min.

[0017] In some specific embodiments, the solid content of the second mixed material in step 2) is 65% to 70%.

[0018] In some specific embodiments, the dispersion rotation speed of the high-speed dispersion stirring in step 3) is 1200rpm~1500rpm, the dispersion revolution speed is 20rpm~25rpm, the dispersion time is 180min~300min, and the vacuum degree is ≤-90MPa.

[0019] Compared with the prior art, the present invention has at least the following advantages:

[0020] 1) The preparation method of the present invention increases the proportion of powder particles (recycled and regenerated lithium iron phosphate powder) content under high solid content conditions of 75% to 80% by adopting a pre-dissolution method, reduces the distance between powder particles, thereby increasing the collision probability between powder particles, and helps the recycled and regenerated lithium iron phosphate powder to collide under high solid content conditions. The recycled and regenerated lithium iron phosphate powder is first soaked with an organic solvent, and then the binder in the recycled and regenerated lithium iron phosphate powder is dissolved in the organic solvent to achieve pre-dissolution of the binder in the recycled and regenerated lithium iron phosphate powder, effectively solving the dispersion difficulty caused by the binder in the recycled and regenerated lithium iron phosphate, reducing the blockage of the screen caused by large particles of the recycled and regenerated lithium iron phosphate positive electrode slurry and the scrapping of particles, scratches, exposed foil, etc. on the appearance of the dried electrode after coating, thereby improving production efficiency and production benefits.

[0021] 2) The preparation method of the present invention recovers and regenerates the lithium iron phosphate powder binder by dissolution, and recycles and reuses it, giving priority to reducing the amount of binder used, thereby achieving the purpose of increasing the proportion of active substances.

[0022] 3) The preparation method of the present invention has a simple process and uses recycled lithium iron phosphate to greatly reduce the cost of the positive electrode and reduce dependence on new mining resources. It also reduces the potential pollution of waste batteries to the environment, making production more environmentally friendly. BRIEF DESCRIPTION OF THE DRAWINGS

[0023] In order to more clearly illustrate the specific embodiments of the present invention, the drawings required for use in the specific embodiments or the description of the prior art will be briefly introduced below.

[0024] Figure 1 This is a SEM image of lithium iron phosphate powder recycled from raw materials used in the present invention;

[0025] Figure 2 The fineness test result of the recycled lithium iron phosphate positive electrode slurry prepared in Example 1 of the present invention;

[0026] Figure 3 The fineness test result of the recycled lithium iron phosphate positive electrode slurry prepared in Comparative Example 1 of the present invention;

[0027] Figure 4 This is a coating effect diagram of the recycled and regenerated lithium iron phosphate positive electrode slurry prepared in Example 1 of the present invention;

[0028] Figure 5 This is a coating effect diagram of the recycled and regenerated lithium iron phosphate positive electrode slurry prepared in Comparative Example 2 of the present invention. DETAILED DESCRIPTION

[0029] The present invention will be further described in detail below in conjunction with the accompanying drawings and embodiments. The following embodiments are only illustrative and not restrictive, and the protection scope of the present invention cannot be limited thereto.

[0030] When a certain amount, concentration or other value or parameter is expressed in the form of a range, a preferred range, or a preferred upper and lower numerical limit, it should be understood that it is equivalent to specifically revealing any range by combining any pair of upper range limits or preferred numerical values ​​with any lower range limit or preferred numerical value, regardless of whether the range is specifically disclosed. Unless otherwise indicated, the numerical range values ​​listed herein include the endpoints of the range, and all integers and fractions within the range.

[0031] Unless otherwise indicated, all percentages, parts, ratios, etc. herein are by weight.

[0032] The materials, methods, and examples herein are illustrative and are not to be construed as limiting unless specifically stated.

[0033] In the following embodiments, the recycled lithium iron phosphate powder is positive electrode lithium iron phosphate powder recycled from waste lithium iron phosphate batteries, and its technical parameters are: D10 ≥ 0.25 μm, D50 = 1.50 ± 1.00 μm, D90 ≤ 10.00 μm, specific surface area = 10.0 ± 3.0 m2 / g, and carbon content 2.0-4.0 wt.%.

[0034] In the following embodiments, the preparation steps of recycling and regenerating lithium iron phosphate powder include:

[0035] Physical separation technology is used to recycle the positive electrode plates of lithium iron phosphate waste, and organic solvents are used for liquid de-powdering. The organic solvents in the powder are removed by high-temperature drying technology at 100℃-200℃, and the recycled lithium iron phosphate is crushed into powder using an efficient crusher. After the crushing, the recycled lithium iron phosphate is sieved and demagnetized to obtain recycled lithium iron phosphate powder;

[0036] Table 1. Differences in incoming lithium iron phosphate materials

[0037] project D50(μm) Specific surface area (㎡ / g) Carbon content (wt.%) Commercially available lithium iron phosphate 1.50±1.00 7.0±3.0 1-2 Recycling of lithium iron phosphate 1.50±1.00 10.0±3.0 2-4

[0038] It can be seen from the table that compared with normal lithium iron phosphate (lithium iron phosphate material purchased on the market), the recycled lithium iron phosphate material has a larger specific surface area and a higher carbon content.

[0039] The organic solvent is any one or more combinations of N-methylpyrrolidone (NMP), N-dimethylamide, dimethyl sulfoxide, ethylene glycol or N-dimethylacetamide; the binder powder is PVDF powder; the conductive agent is one or more combinations of carbon nanotubes, conductive graphene, conductive carbon black, and carbon fibers; and the dispersant is polyvinyl pyrrolidone.

[0040] Example 1

[0041] This embodiment provides a method for preparing a recycled lithium iron phosphate positive electrode slurry, which comprises the following steps:

[0042] 1) Recycle the regenerated lithium iron phosphate powder (such as Figure 1 As shown) and N-methylpyrrolidone (NMP) are added in a mass ratio of 75:25, mixed at a high solid content of 75% (the solid content in this application refers to the proportion of solid powder in the entire system), and dispersed and pre-dissolved at a rotation speed of 1300 rpm, a revolution speed of 25 rpm, and a dispersion time of 180 min to obtain a first mixed material with a solid content of 75%;

[0043] 2) Adding binder powder PVDF, conductive agent SP, and N-methylpyrrolidone (NMP) to the first mixture obtained in step 1), mixing and dispersing and stirring to obtain a second mixture with a solid content of 69.5%;

[0044] The mass ratio of the recycled lithium iron phosphate powder, binder powder, conductive agent and dispersant is: 98.2:0.5:1.2:0.1;

[0045] 3) Add polyvinyl pyrrolidone and N-methyl pyrrolidone (NMP) to the second mixture obtained in step 2) to obtain a mixture with a solid content of 68.0% of the recycled lithium iron phosphate powder, and then evacuate and rotate at a speed of 1500 rpm, a revolution speed of 25 rpm, a dispersion time of 180 min, and disperse and stir at a vacuum degree of ≤-90 MPa. After the stirring is completed, slowly stir to defoam to obtain a recycled lithium iron phosphate positive electrode slurry.

[0046] Example 2

[0047] This embodiment provides a method for preparing a recycled lithium iron phosphate positive electrode slurry, which comprises the following steps:

[0048] 1) adding recycled lithium iron phosphate powder and N-methylpyrrolidone (NMP) in a mass ratio of 80:20, mixing at a high solid content of 80%, and dispersing and pre-dissolving at a rotation speed of 1300 rpm, a revolution speed of 25 rpm, and a dispersion time of 240 min to obtain a first mixed material with a solid content of 80%;

[0049] 2) Adding binder powder PVDF, conductive agent SP, and N-methylpyrrolidone (NMP) to the first mixture obtained in step 1), mixing and dispersing and stirring to obtain a second mixture with a solid content of 69.5%;

[0050] The mass ratio of the recycled lithium iron phosphate powder, binder powder, conductive agent and dispersant is: 97.5:0.8:1.5:0.2;

[0051] 3) Add polyvinyl pyrrolidone and N-methyl pyrrolidone (NMP) to the second mixture obtained in step 2) to obtain a mixture with a solid content of 68.0% of the recycled lithium iron phosphate powder, and then evacuate and rotate at a speed of 1300 rpm, a revolution speed of 25 rpm, a dispersion time of 300 min, and disperse and stir at a vacuum degree of ≤-90 MPa. After the stirring is completed, slowly stir to defoam to obtain a recycled lithium iron phosphate positive electrode slurry.

[0052] Example 3

[0053] This embodiment provides a method for preparing a recycled lithium iron phosphate positive electrode slurry, which comprises the following steps:

[0054] 1) adding recycled lithium iron phosphate powder and N-methylpyrrolidone (NMP) in a mass ratio of 75:25, mixing at a high solid content of 75%, and dispersing and pre-dissolving at a rotation speed of 1250 pm, a revolution speed of 25 rpm, and a dispersion time of 180 min to obtain a first mixed material with a solid content of 75%;

[0055] 2) Adding binder powder PVDF, conductive agent SP, and N-methylpyrrolidone (NMP) to the first mixture obtained in step 1), mixing and dispersing and stirring to obtain a second mixture with a solid content of 69.5%;

[0056] The mass ratio of the recycled lithium iron phosphate powder, binder powder, conductive agent and dispersant is: 98.8:0.3:0.8:0.1;

[0057] 3) Add polyvinyl pyrrolidone and N-methyl pyrrolidone (NMP) to the second mixture obtained in step 2) to obtain a mixture with a solid content of 68.0% of the recycled lithium iron phosphate powder, then evacuate and rotate at a speed of 1200 rpm, a revolution speed of 20 rpm, a dispersion time of 240 min, and disperse and stir at a vacuum degree of ≤-90 MPa, and then slowly stir to defoam to obtain a recycled lithium iron phosphate positive electrode slurry.

[0058] Comparative Example 1

[0059] This comparative example provides a method for preparing a recycled lithium iron phosphate positive electrode slurry, which is basically the same as Example 1, except that the lithium iron phosphate in step 1) is non-recycled lithium iron phosphate (i.e., commercially purchased lithium iron phosphate as raw material), specifically:

[0060] Non-recoverable lithium iron phosphate and the first portion of organic solvent NMP are added in a ratio of 75:25, mixed at a high solid content of 75%, the dispersion rotation speed is 1300rpm, the dispersion revolution speed is 25rpm, the dispersion time is 180min, and high-speed dispersion pre-dissolution is performed to obtain a first mixed material with a solid content of 75%.

[0061] Comparative Example 2

[0062] This comparative example provides a preparation method for recycling and regenerating lithium iron phosphate positive electrode slurry, which is basically the same as Example 1, except that the solid content of the first mixed material in step 1) is 70%, specifically:

[0063] 1) Recycled lithium iron phosphate powder and N-methylpyrrolidone (NMP) are added in a mass ratio of 70:30, mixed at a high solid content of 70%, and dispersed and pre-dissolved at a rotation speed of 1300 rpm, a revolution speed of 25 rpm, and a dispersion time of 180 min to obtain a first mixed material with a solid content of 70%.

[0064] Comparative Example 3

[0065] This comparative example provides a preparation method for recycled regenerated lithium iron phosphate positive electrode slurry, which is basically the same as Example 1, except that the mass ratios of the recycled regenerated lithium iron phosphate powder, binder powder, conductive agent, and dispersant in step 2) are different, specifically:

[0066] 2) Adding binder powder PVDF, conductive agent SP, and N-methylpyrrolidone (NMP) to the first mixture obtained in step 1), mixing and dispersing and stirring to obtain a second mixture with a solid content of 69.5%;

[0067] The mass ratio of the recycled lithium iron phosphate powder, binder powder, conductive agent and dispersant is: 96.6:1.8:1.5:0.1;

[0068] Performance test example:

[0069] This application takes Example 1 as an example, and performs performance tests on the lithium iron phosphate positive electrode slurries prepared in Example 1 and Comparative Examples 1-3, as shown in Table 1:

[0070] project Viscosity (mPa·s) Fineness(μm) Discharging and coating phenomena Example 1 10589 3 There is no abnormality in the discharge, and there are no particles or scratches on the coated pole piece. Example 2 12893 4 There is no abnormality in the discharge, and there are no particles or scratches on the coated pole piece. Example 3 8371 3 There is no abnormality in the discharge, and there are no particles or scratches on the coated pole piece. Comparative Example 1 2088 3 There is no abnormality in the discharge, but the slurry is too thin to be coated Comparative Example 2 11899 28 There are many particles in the discharged material after screening, and there are particles in the coated electrode Comparative Example 3 —— 5 The viscosity is too high and exceeds the range, so it cannot be tested and the slurry cannot be discharged and coated.

[0071] From the test data in Table 1, it can be seen that the recovered regenerated lithium iron phosphate positive electrode slurry obtained by the preparation method of the present invention (Example 1) is uniform and the discharge is smooth, and the fineness test is 3μm (such as Figure 2 As shown), the coated pole piece has no particle scratches (as shown Figure 4 shown).

[0072] The positive electrode slurry obtained by using non-recyclable lithium iron phosphate (Comparative Example 1) has poor stability, with a fineness test of 3μm. There are no particle scratches on the coated electrode, but the coating has obvious wavy edges and cannot be used. This is mainly because there is no recyclable and reusable binder in the non-recyclable lithium iron phosphate. The slurry is easy to disperse but a large amount of binder is required, otherwise the slurry cannot be formed in a stable state.

[0073] The viscosity of the positive electrode slurry obtained by the non-high solid content pre-dissolution scheme (Comparative Example 2) is stable, but the screen is blocked during the discharging process. The fineness test is 28μm, and there are large particles (such as Figure 3 As shown in the figure), the coated electrode has many pits and particle scratches (as shown in the figure). Figure 5 The defect rate is high, which is mainly due to the low solid content during pre-dissolution, and the recovered lithium iron phosphate with binder cannot be well dispersed.

[0074] The commercially available lithium iron phosphate formula (Comparative Example 3) was used to increase the proportion of binder in the recycled lithium iron phosphate powder. The viscosity of the positive electrode slurry prepared was too high to exceed the test range, and the slurry could not be coated. The main reason was that the binder in the recycled lithium iron phosphate could be recycled, and adding too much binder caused the slurry viscosity to be too high to be used. This shows that the recycled lithium iron phosphate positive electrode slurry obtained by the preparation process of the present invention can reduce the use of binder, and the slurry is stable, the discharge is smooth, and there is no particle scratch on the coating appearance.

[0075] The above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein by equivalents. These modifications or replacements do not make the essence of the corresponding technical solutions deviate from the scope of the technical solutions of the embodiments of the present invention, and they should all be included in the scope of the claims and specification of the present invention.

Claims

1. A method for preparing a recycled lithium iron phosphate positive electrode slurry, characterized in that: The steps include: 1) mixing the recovered regenerated lithium iron phosphate powder and the organic solvent and pre-dissolving them by high-speed dispersion to obtain a first mixed material; 2) adding binder powder, conductive agent and organic solvent to the first mixed material obtained in step 1), mixing and dispersing and stirring to obtain a second mixed material; 3) Adding a dispersant and an organic solvent to the second mixed material obtained in step 2), performing high-speed dispersion and stirring under vacuum conditions, and performing slow stirring and defoaming after the dispersion is completed to obtain a recovered regenerated lithium iron phosphate positive electrode slurry.

2. The method for preparing the recycled lithium iron phosphate positive electrode slurry according to claim 1, characterized in that: The recycled lithium iron phosphate powder in step 1) is the positive electrode lithium iron phosphate powder recycled from waste lithium iron phosphate batteries.

3. The method for preparing the recycled lithium iron phosphate positive electrode slurry according to claim 2, characterized in that: The recycled lithium iron phosphate powder has D10≥0.25 μm, D50=1.50±1.00 μm, D90≤10.00 μm, specific surface area=10.0±3.0 m2 / g, and carbon content 2.0-4.0 wt.%.

4. The method for preparing the recycled and regenerated lithium iron phosphate positive electrode slurry according to claim 1, characterized in that: The organic solvent is any one or more combinations of N-methylpyrrolidone (NMP), N-dimethylamide, dimethyl sulfoxide, ethylene glycol or N-dimethylacetamide; the binder powder is PVDF powder; the conductive agent is one or more combinations of carbon nanotubes, conductive graphene, conductive carbon black, and carbon fibers; and the dispersant is polyvinyl pyrrolidone.

5. The method for preparing the recycled lithium iron phosphate positive electrode slurry according to claim 1, characterized in that: The mass ratio of the recycled lithium iron phosphate powder, the binder powder, the conductive agent and the dispersant is: 99.1-97.5: 0.3-0.8: 0.5-1.5: 0.1-0.

2.

6. The method for preparing the recycled lithium iron phosphate positive electrode slurry according to claim 1, characterized in that: In step 1), the amount of the first organic solvent added is 20% to 25% of the total mass of the first mixed material, and the solid content of the first mixed material is 75% to 80%.

7. The method for preparing the recycled lithium iron phosphate positive electrode slurry according to claim 2, characterized in that: The high-speed dispersion pre-dissolution in step 1) has a dispersion rotation speed of 1200rpm to 1500rpm, a dispersion revolution speed of 20rpm to 25rpm, and a dispersion time of 120min to 240min.

8. The method for preparing the recycled lithium iron phosphate positive electrode slurry according to claim 7, characterized in that: In step 2), the solid content of the second mixed material is 65% to 70%.

9. The method for preparing the recycled lithium iron phosphate positive electrode slurry according to claim 8, characterized in that: The high-speed dispersing stirring in step 3) has a dispersing rotation speed of 1200rpm to 1500rpm, a dispersing revolution speed of 20rpm to 25rpm, a dispersing time of 180min to 300min, and a vacuum degree of ≤-90MPa.